Dincolo de cheltuieli: măsurarea impactului economic al Bibliotecii Municipale „B.P. Hasdeu” - COȘERI, Tatiana (BIBLIOPOLIS, 2026)
The article highlights the importance of the economic impact for the library, providing examples of calculating the return on financial investments in the library.